Bilingual deaf and hearing families : narrative interviews - Bodner-Johnson, Barbara (Gallaudet University Press, 2012)
This study emphasizes the importance of family support for deaf members, particularly through the use of both American Sign Language (ASL) and spoken and/or written English. Research has shown how these factors influence such areas as a child's development, performance in school, and relationships with brothers and sisters. In this volume, authors Barbara Bodner-Johnson and Beth S. Benedict concentrate on the vital, positive effects of bilingualism and how families that share their experiences with other families can enhance all of their children's achievement and enrichment. Bilingual Deaf and Hearing Families: Narrative Interviews describes the experiences of ten families who have at least one deaf family member. In five of the families, the parents are hearing and they have a deaf child; two of the children in these families have cochlear implants. In three families, both the parents and children are deaf. In one family, the parents are deaf and their daughter is hearing; and in one family, the parents and one child are deaf and they all have cochlear implants, and the deaf child's twin is hearing. The interviews were conducted in the families' homes using set topics and questions. The family discussions cover a wide range of subjects: cochlear implants, where they live, their thoughts about family relationships, how they participate in the Deaf community, how they arrive at certain decisions, their children's friendships, and the goals and resiliencies they have as a family.